Comparison of clinical outcomes of drug-coated balloons angioplasty vs. plain old balloons angioplasty for peripheral arterial disease: an umbrella meta-analysis - Li, Jiacheng; Lu, Wei; Lin, Lihong; Wu, Jiawen; Cheng, Guobing; Hu, Qiang; Guo, Yi (Frontiers in Cardiovascular Medicine, 2024)
BackgroundPeripheral artery disease (PAD) affects millions globally, causing significant morbidity. Traditional treatments like plain old balloon angioplasty (POBA) have limited success due to high restenosis rates. Drug-coated balloon angioplasty (DCBA) has emerged as a promising alternative, locally delivering antiproliferative drugs like paclitaxel to reduce restenosis. However, the clinical outcomes of DCBA compared to POBA remain inconsistent across various studies.ObjectiveThis umbrella meta-analysis aimed to compare the clinical outcomes of DCBA and POBA in PAD patients, synthesizing data from multiple meta-analyses to provide a more robust evidence base.MethodsWe conducted an umbrella meta-analysis following PRISMA guidelines, systematically reviewing Cochrane Library, Embase, PubMed, and Web of Science. Studies were included if they compared DCBA and POBA in PAD patients, focusing on primary outcomes such as target lesion revascularization (TLR), primary patency (PP), all-cause mortality (ACM), and amputation. Secondary outcomes included restenosis, late lumen loss (LLL), and major adverse events (MAE).ResultsSixteen meta-analyses were included. DCBA significantly reduced the risk of TLR (OR: 0.41, 95% CI: 0.34–0.49), PP was significantly higher in DCBA (OR: 2.05, 95% CI: 1.53–2.75), and restenosis was lower (OR: 0.46, 95% CI: 0.41–0.51). No significant differences were found in ACM or amputation risk between the two groups. Heterogeneity was moderate to high across most outcomes.ConclusionDCBA provides significant advantages over POBA in reducing TLR and restenosis while maintaining vessel patency. However, the effects on ACM and amputation remain inconclusive. Future research should focus on long-term safety and identifying which patient subgroups benefit most from DCBA.Systematic Review Registrationhttps://www.crd.york.ac.uk/, PROSPERO [CRD42024591967].